Influence of drying temperature on the mechanical properties of popcorn kernels - PAIVA, Yuri de Brito; ARAUJO, Ana Claudia Sátiro de; GIONGO, Pedro Rogério; LIMA, Dienifer de Araújo; SANTOS, Wellysson Rafael Costa; TAVEIRA, José Henrique da Silva (Food Science and Technology, 2025)
High drying rates render desiccation protection mechanisms inefficient in grains, potentially resulting in increased susceptibility to cracks and breaks. Thus, the present study aimed to evaluate the impact of drying temperature and moisture content on the mechanical properties of popcorn kernels, determining the proportional deformity modulus, rupture force, and maximum compression force. Popcorn kernels with different moisture contents were used, dried at temperatures of 40°C, 60°C, and 40/60°C. The kernels were subjected to individual uniaxial compression, in their natural resting position, at 0.001 m s−1. The results indicate that the compression force required to deform the popcorn kernels and the proportional deformity modulus increased with a decrease in the moisture content, regardless of the drying temperature. The rupture point or “bioyield point” increased as the moisture content decreased, with temperature being an influential factor in determining the point. The temperature of 60°C had the worst average for moisture content below 0.198 dry basis for the rupture force parameter, while the temperature of 40/60°C stood out from the others due to the longer induction time for the membrane desiccation protection mechanism.